PENGARUH SHARIAH COMPLIANCE DAN ISLAMIC CORPORATE GOVERNANCE TERHADAP FRAUD DI BANK SYARIAH - Muhammad Wahyu Cahyadi, - (2019)
This study aims to examine the influence of shariah compliance and Islamic corporate governance against fraud in Islamic banks. Independent variables used are shariah compliance with the Profit Sharing Ratio and Islamic Investment Ratio as a proxy and Islamic corporate governance. The dependent variable used is fraud in Islamic banks. The population in this study are all Islamic Banks (BUS) which is registered in Bank Indonesia in the period 2010 to 2017. The sample was selected using purposive sampling method. Total samples used in this study were 8 Islamic Banks with 8-year study period. The analytical method used in this study is multiple regression were processed using SPSS version 25. The results of this study indicate that the shariah compliance with the Profit Sharing Ratio as a proxy and Islamic Corporate Governance has significant influence on Islamic bank's fraud while Islamic Investment Ratio has no a significant influence on fraud in Islamic banks.